Sei sulla pagina 1di 29

The Mathematics Digital Library (mathematics-dl.

org)

Solutions to Exercise 1.1


(Ho Soo Thong, David Khor Nyak Hiong and Yan
Kow Cheong’s Additional Maths 360 ‒ ISBN
9789810117481)

Solved by:
Dr Lee Chu Keong
(ascklee@gmail.com)

This file contains sample solutions from mathematics-dl.org. To


obtain the complete set of solutions for Additional Maths 360,
please go to http://mathematics-dl.org/subscribe.

0
The Mathematics Digital Library (mathematics-dl.org)

Exercise 1.1 (p. 5‒6)


Basic (Questions 15)
Question 1(a)
𝑦 = 2𝑥 + 1 … (1)
𝑦 = 𝑥 2 + 2𝑥 − 3 … (2)

Equating (1) and (2) and factorising:


2𝑥 + 1 = 𝑥 2 + 2𝑥 − 3
0 = 𝑥2 − 4
= (𝑥 + 2)(𝑥 − 2)

𝑥−2=0 𝑥+2=0
𝑥=2 𝑥 = −2
Substituting 𝑥 = 2 into (1): Substituting 𝑥 = −2 into (1):
𝑦 = 2(2) + 1 𝑦 = 2(−2) + 1
= 4+1 = −4 + 1
=5 = −3
(2, 5) (−2, −3)

1
The Mathematics Digital Library (mathematics-dl.org)

Question 1(b)
𝑦 = 2 + 𝑥 … (1)
𝑦 = 2𝑥 2 − 5𝑥 − 6 … (2)

Equating (1) and (2):


2 + 𝑥 = 2𝑥 2 − 5𝑥 − 6

Rearranging and factorising:


0 = 2𝑥 2 − 6𝑥 − 8
= 2(𝑥 2 − 3𝑥 − 4)
= 2(𝑥 − 4)(𝑥 + 1)

𝑥−4=0 𝑥+1=0
𝑥=4 𝑥 = −1
Substituting 𝑥 = 4 into (1): Substituting 𝑥 = −1 into (1):
𝑦 =𝑥+2 𝑦 =𝑥+2
=4+2 = −1 + 2
=6 =1
(4, 6) (−1, 1)

2
The Mathematics Digital Library (mathematics-dl.org)

Question 1(c)
𝑦 = 4 − 2𝑥 … (1)
𝑦 2 − 4𝑥 = 0 … (2)

Substituting (1) into (2):


(4 − 2𝑥)2 − 4𝑥 = 0
(16 + 4𝑥 2 − 16𝑥) − 4𝑥 = 0
16 + 4𝑥 2 − 16𝑥 − 4𝑥 = 0
4𝑥 2 − 20𝑥 + 16 = 0

Factorising:
4(𝑥 2 − 5𝑥 + 4) = 0
4(𝑥 − 4)(𝑥 − 1) = 0

𝑥−4=0 𝑥−1=0
𝑥=4 𝑥=1
Substituting 𝑥 = 4 into (1): Substituting 𝑥 = 1 into (1):
𝑦 = 4 − 2𝑥 𝑦 = 4 − 2𝑥
= 4 − 2(4) = 4 − 2(1)
= 4−8 = 4−2
= −4 =2
(4, −4) (1, 2)

3
The Mathematics Digital Library (mathematics-dl.org)

Question 2(a)
𝑦 = 2 − 𝑥 … (1)
2𝑥 2 + 𝑥𝑦 + 1 = 0 … (2)

Substituting (1) into (2):


2𝑥 2 + 𝑥(2 − 𝑥) + 1 = 0
2𝑥 2 + 2𝑥 − 𝑥 2 + 1 = 0
𝑥 2 + 2𝑥 + 1 = 0

Factorising:
(𝑥 + 1)2 = 0

𝑥+1=0
𝑥 = −1

Substituting 𝑥 = −1 into equation (1):


𝑦 = 2−𝑥
= 2 − (−1)
= 2+1
=3

Solution: (−1, 3)

4
The Mathematics Digital Library (mathematics-dl.org)

Question 2(b)
𝑦 = 1 − 3𝑥 … (1)
𝑥 2 + 𝑦 2 = 5 … (2)

Substituting (1) into (2):


𝑥 2 + (1 − 3𝑥)2 = 5
𝑥 2 + (1 + 9𝑥 2 − 6𝑥) = 5
𝑥 2 + 1 + 9𝑥 2 − 6𝑥 = 5
10𝑥 2 − 6𝑥 − 4 = 0
Factorising:
2(5𝑥 2 − 3𝑥 − 2) = 0
5𝑥 2 − 3𝑥 − 2 = 0
(5𝑥 + 2)(𝑥 − 1) = 0

5𝑥 + 2 = 0 𝑥−1=0
5𝑥 = −2 𝑥=1
2
𝑥=−
5
2
Substituting 𝑥 = − 5 into (1): Substituting 𝑥 = 1 into (1):
𝑦 = 1 − 3𝑥
𝑦 = 1 − 3𝑥
2 = 1 − 3(1)
= 1 − 3 (− )
5 = 1−3
6 = −2
= 1+
5
1
=2
5
2 1 (1, −2)
(− , 2 )
5 5

5
The Mathematics Digital Library (mathematics-dl.org)

Question 2(c)
3𝑥 + 2𝑦 = 1 … (1)
3𝑥 2 + 2𝑦 2 = 11 … (2)

From (1):
3𝑥 = 1 − 2𝑦
1 2
∴𝑥= − 𝑦 … (3)
3 3

Substituting (3) into (2):


1 2 2
3 ( − 𝑦) + 2𝑦 2 = 11
3 3
1 4 4
3 ( + 𝑦 2 − 𝑦) + 2𝑦 2 = 11
9 9 9

Multiplying throughout by 3:
(1 + 4𝑦 2 − 4𝑦) + 6𝑦 2 = 33
1 + 4𝑦 2 − 4𝑦 + 6𝑦 2 = 33

Rearranging and factorising:


10𝑦 2 − 4𝑦 − 32 = 0
2(5𝑦 2 − 2𝑦 − 16) = 0
2(5𝑦 + 8)(𝑦 − 2) = 0

5𝑦 + 8 = 0 𝑦−2=0
5𝑦 = −8 𝑦=2
8
𝑦=−
5
3
= −1
5
8
Substituting 𝑦 = − 5 into (3): Substituting 𝑦 = 2 into (3):
1 2
1 2 𝑥= − 𝑦
𝑥= − 𝑦 3 3
3 3
1 2
1 2 8 = − (2)
= − (− ) 3 3
3 3 5

6
The Mathematics Digital Library (mathematics-dl.org)

1 16 1 4
= + = −
3 15 3 3
5 16 3
= + =−
15 15 3
21 = −1
=
15
7
=
5
2
=1
5
2 3 (−1, 2)
(1 , −1 )
5 5

7
The Mathematics Digital Library (mathematics-dl.org)

Question 3
𝑦 = 8 − 𝑥 … (1)
𝑥2 𝑦
+ = 3 … (2)
4 3

Substituting (1) into (2), and rearranging:


𝑥2 8 − 𝑥
+ =3
4 3
𝑥2 8 𝑥
+ − =3
4 3 3
𝑥2 1 𝑥
− − =0
4 3 3

Multiplying throughout by 12 (the LCM of 3 and 4):


3𝑥 2 − 4 − 4𝑥 = 0

Rearranging and factorising:


3𝑥 2 − 4𝑥 − 4 = 0
(3𝑥 + 2)(𝑥 − 2) = 0

3𝑥 + 2 = 0 𝑥−2=0
3𝑥 = −2 𝑥=2
2
𝑥=−
3

2
The 𝑥-coordinates are − 3 and 2.

8
The Mathematics Digital Library (mathematics-dl.org)

Question 4(i)
Perimeter of the first square:
𝑥 + 𝑥 + 𝑥 + 𝑥 = 4𝑥
Perimeter of the second square:
𝑦 + 𝑦 + 𝑦 + 𝑦 = 4𝑦

Sum of the perimeters of the two squares:


4𝑥 + 4𝑦 = 32
4(𝑥 + 𝑦) = 32

Dividing throughout by 4:
𝑥+𝑦 =8
𝑦 = 8 − 𝑥 … (1)

Question 4(ii)
Area of the first square:
𝑥 × 𝑥 = 𝑥2
Area of the second square:
𝑦 × 𝑦 = 𝑦2

Sum of the areas of the two squares:


𝑥 2 + 𝑦 2 = 34 … (2)

Question 4(iii)
Solve (1) and (2) simultaneously:
Substituting (1) into (2):
𝑥 2 + (8 − 𝑥)2 = 34
Expanding:
𝑥 2 + (64 + 𝑥 2 − 16𝑥) = 34
𝑥 2 + 64 + 𝑥 2 − 16𝑥 = 34
Rearranging and factorising:
2𝑥 2 − 16𝑥 + 30 = 0
2(𝑥 2 − 8𝑥 + 15) = 0

9
The Mathematics Digital Library (mathematics-dl.org)

𝑥 2 − 8𝑥 + 15 = 0
Factorising:
(𝑥 − 3)(𝑥 − 5) = 0
𝑥−3=0 𝑥−5=0
𝑥=3 𝑥=5
𝑦 =8−𝑥 𝑦 =8−𝑥
=8−3 =8−5
=5 =3

Solution: 3 cm and 5 cm

10
The Mathematics Digital Library (mathematics-dl.org)

Question 5(i)
𝐴𝑟𝑒𝑎 = 𝑥𝑦
𝑃𝑒𝑟𝑖𝑚𝑒𝑡𝑒𝑟 = 2𝑥 + 2𝑦
= 2(𝑥 + 𝑦)

Question 5(ii)
216 = 𝑥𝑦 … (1)
60 = 2(𝑥 + 𝑦) … (2)
Dividing throughout by 2:
30 = 𝑥 + 𝑦 … (3)
Rearranging:
𝑦 = 30 − 𝑥 … (4)
Substituting (4) into (1):
216 = 𝑥(30 − 𝑥)
Multiplying out:
216 = 30𝑥 − 𝑥 2
Rearranging:
𝑥 2 − 30𝑥 + 216 = 0
Factorising:
(𝑥 − 12)(𝑥 − 18) = 0

𝑥 − 12 = 0 𝑥 − 18 = 0
𝑥 = 12 𝑥 = 18
𝑦 = 30 − 𝑥 𝑦 = 30 − 𝑥
= 30 − 12 = 30 − 18
= 18 = 12
Solution: 12 m and 18 m

11
The Mathematics Digital Library (mathematics-dl.org)

Intermediate (Question 610)


Question 6(a)
2𝑦 = 3𝑥 − 1 … (1)
(𝑥 − 2)2 + (2𝑦 + 3)2 = 26 … (2)
Substituting (1) into (2):
(𝑥 − 2)2 + (3𝑥 − 1 + 3)2 = 26
(𝑥 − 2)2 + (3𝑥 + 2)2 = 26
Multiplying out:
(𝑥 2 − 4𝑥 + 4) + (9𝑥 2 + 4 + 12𝑥) = 26
𝑥 2 − 4𝑥 + 4 + 9𝑥 2 + 4 + 12𝑥 = 26
Rearranging:
10𝑥 2 + 8𝑥 − 18 = 0
Dividing throughout by 2:
5𝑥 2 + 4𝑥 − 9 = 0
Factorising:
(5𝑥 + 9)(𝑥 − 1) = 0

5𝑥 + 9 = 0 𝑥−1=0
5𝑥 = −9 𝑥=1
9
𝑥=−
5
4
= −1
5
9
Substituting 𝑥 = − 5 into (1): Substituting 𝑥 = 1 into (1):
2𝑦 = 3𝑥 − 1
2𝑦 = 3𝑥 − 1
9 = 3(1) − 1
= 3 (− ) − 1
5 =2
27 𝑦=1
=− −1
5
32
=−
5
16
𝑦=−
5
1
= −3
5

12
The Mathematics Digital Library (mathematics-dl.org)

4 1 (1,1)
(−1 , −3 )
5 5

13
The Mathematics Digital Library (mathematics-dl.org)

Question 6(b)
𝑥 = 2 + 2𝑦 … (1)
𝑥 2 − 2𝑥𝑦 + 𝑦 2 = 1 … (2)
Substituting (1) into (2):
(2 + 2𝑦)2 − 2(2 + 2𝑦)𝑦 + 𝑦 2 = 1
(4 + 8𝑦 + 4𝑦 2 ) − (4𝑦 + 4𝑦 2 ) + 𝑦 2 = 1
4 + 8𝑦 + 4𝑦 2 − 4𝑦 − 4𝑦 2 + 𝑦 2 = 1
𝑦 2 + 4𝑦 + 3 = 0
Factorising:
(𝑦 + 3)(𝑦 + 1) = 0

𝑦+3=0 𝑦+1=0
𝑦 = −3 𝑦 = −1
𝑥 = 2 + 2𝑦 𝑥 = 2 + 2𝑦
= 2 + 2(−3) = 2 + 2(−1)
=2−6 =2−2
= −4 =0
(−4, −3) (0, −1)

14
The Mathematics Digital Library (mathematics-dl.org)

Question 6(c)
𝑥 = 3𝑦 − 3 … (1)
2 1
− = 2 … (2)
3𝑦 𝑥
Substituting (1) into (2):
2 1
− =2
3𝑦 3𝑦 − 3
2(3𝑦 − 3) − 3𝑦
=2
3𝑦(3𝑦 − 3)
6𝑦 − 6 − 3𝑦
=2
9𝑦 2 − 9𝑦
3𝑦 − 6
=2
9𝑦 2 − 9𝑦
3(𝑦 − 2)
=2
3(3𝑦 2 − 3𝑦)
𝑦−2
=2
3𝑦 2 − 3𝑦

𝑦 − 2 = 2(3𝑦 2 − 3𝑦)
= 6𝑦 2 − 6𝑦
Rearranging:
6𝑦 2 − 7𝑦 + 2 = 0
Factorising:
(3𝑦 − 2)(2𝑦 − 1) = 0

3𝑦 − 2 = 0 2𝑦 − 1 = 0
3𝑦 = 2 2𝑦 = 1
2 1
𝑦= 𝑦=
3 2
𝑥 = 3𝑦 − 3 𝑥 = 3𝑦 − 3
2 1
= 3( ) − 3 = 3( ) − 3
3 2
= 2−3 3
= −3
= −1 2
3
=−
2

15
The Mathematics Digital Library (mathematics-dl.org)

1
= −1
2
2 1 1
(−1, ) (−1 , )
3 2 2

16
The Mathematics Digital Library (mathematics-dl.org)

Question 7(a)
𝑥 = 2𝑦 + 3 … (1)
𝑥𝑦 + 20 = 5𝑥 … (2)
Substituting (1) into (2):
(2𝑦 + 3)𝑦 + 20 = 5(2𝑦 + 3)
Expanding:
(2𝑦 2 + 3𝑦) + 20 = 10𝑦 + 15
2𝑦 2 + 3𝑦 + 20 = 10𝑦 + 15
Rearranging:
2𝑦 2 − 7𝑦 + 5 = 0
Factorising:
(2𝑦 − 5)(𝑦 − 1) = 0

2𝑦 − 5 = 0 𝑦−1=0
2𝑦 = 5 𝑦=1
5
𝑦=
2
1
=2
2
𝑥 = 2𝑦 + 3 𝑥 = 2𝑦 + 3
5 = 2(1) + 3
= 2( ) + 3
2 = 2+3
= 5+3
=5
=8
1 (5, 1)
(8, 2 )
2

Question 7(b)
𝑦 = 2𝑥 − 4 … (1)
2𝑥 2 + 4𝑥𝑦 − 3𝑦 = 0 … (2)
Substituting (1) into (2):
2𝑥 2 + 4𝑥(2𝑥 − 4) − 3(2𝑥 − 4) = 0
Expanding:
2𝑥 2 + (8𝑥 2 − 16𝑥) − (6𝑥 − 12) = 0

17
The Mathematics Digital Library (mathematics-dl.org)

2𝑥 2 + 8𝑥 2 − 16𝑥 − 6𝑥 + 12 = 0
Rearranging:
10𝑥 2 − 22𝑥 + 12 = 0
Dividing throughout by 2:
5𝑥 2 − 11𝑥 + 6 = 0
Factorising:
(5𝑥 − 6)(𝑥 − 1) = 0

5𝑥 − 6 = 0 𝑥−1=0
5𝑥 = 6 𝑥=1
6
𝑥=
5
1
=1
5
6
Substituting 𝑥 = 5 into (1): Substituting 𝑥 = 1 into (1):
𝑦 = 2𝑥 − 4
𝑦 = 2𝑥 − 4
6 = 2(1) − 4
= 2( ) − 4
5 = 2−4
12 20 = −2
= −
5 5
8
=−
5
3
= −1
5
1 3 (1, −2)
(1 , −1 )
5 5

18
The Mathematics Digital Library (mathematics-dl.org)

Question 7(c)
𝑦 = 1 − 3𝑥 … (1)
(𝑥 + 𝑦)(𝑥 + 2𝑦) = 3 … (2)
Substituting (1) into (2):
(𝑥 + 1 − 3𝑥)(𝑥 + 2(1 − 3𝑥)) = 3
(1 − 2𝑥)(𝑥 + 2 − 6𝑥) = 3
(1 − 2𝑥)(2 − 5𝑥) = 3
Multiplying out:
2 − 5𝑥 − 4𝑥 + 10𝑥 2 = 3
Rearranging:
10𝑥 2 − 9𝑥 − 1 = 0
Factorising:
(10𝑥 + 1)(𝑥 − 1) = 0

10𝑥 + 1 = 0 𝑥−1=0
10𝑥 = −1 𝑥=1
1
𝑥=−
10
𝑦 = 1 − 3𝑥 𝑦 = 1 − 3𝑥
1 = 1 − 3(1)
= 1 − 3 (− )
10 = 1−3
3
=1+ = −2
10
3
=1
10
1 3 (1, −2)
(− , 1 )
10 10

19
The Mathematics Digital Library (mathematics-dl.org)

Question 8
𝑦 = 3𝑥 − 2 … (1)
2𝑥 𝑦
+ = 3 … (2)
𝑦 𝑥
Substituting (1) into (2):
2𝑥 3𝑥 − 2
+ =3
3𝑥 − 2 𝑥

2𝑥 2 + (3𝑥 − 2)2
=3
𝑥(3𝑥 − 2)
2𝑥 2 + (9𝑥 2 + 4 − 12𝑥)
=3
3𝑥 2 − 2𝑥
2𝑥 2 + 9𝑥 2 + 4 − 12𝑥
=3
3𝑥 2 − 2𝑥
11𝑥 2 + 4 − 12𝑥
=3
3𝑥 2 − 2𝑥
Cross-multiplying:
11𝑥 2 + 4 − 12𝑥 = 3(3𝑥 2 − 2𝑥)
11𝑥 2 + 4 − 12𝑥 = 9𝑥 2 − 6𝑥
Rearranging:
2𝑥 2 − 6𝑥 + 4 = 0
Dividing throughout by 2:
𝑥 2 − 3𝑥 + 2 = 0
Factorising:
(𝑥 − 2)(𝑥 − 1) = 0

𝑥−2=0 𝑥−1=0
𝑥=2 𝑥=1
Substituting 𝑥 = 2 into (1): Substituting 𝑥 = 1 into (1):
𝑦 = 3𝑥 − 2 𝑦 = 3𝑥 − 2
= 3(2) − 2 = 3(1) − 2
= 6−2 = 3−2
=4 =1
(2, 4) (1, 1)

20
The Mathematics Digital Library (mathematics-dl.org)

Question 9
Using Pythagoras Theorem:
(4𝑥)2 + (3𝑥)2 = 152
16𝑥 2 + 9𝑥 2 = 225
25𝑥 2 = 225

Dividing throughout by 25:


225
𝑥2 =
25
=9

𝑥 = ±3
The dimensions: 9 in by 12 in

21
The Mathematics Digital Library (mathematics-dl.org)

Question 10(i)
Using Pythagoras Theorem:
𝑥 2 + 𝑦 2 = 52
𝑥 2 + 𝑦 2 = 25 … (1)

Question 10(ii)
𝑦 = 1 + 𝑥 … (2)

Solve (1) and (2) simultaneously:


Substituting (1) into (2):
𝑥 2 + (1 + 𝑥)2 = 25
𝑥 2 + (1 + 𝑥 2 + 2𝑥) = 25
𝑥 2 + 1 + 𝑥 2 + 2𝑥 = 25
2𝑥 2 + 2𝑥 − 24 = 0
Dividing throughout by 2:
𝑥 2 + 𝑥 − 12 = 0
Factorising:
(𝑥 + 4)(𝑥 − 3) = 0

𝑥+4=0 𝑥−3=0
𝑥 = −4 𝑥=3
Substituting 𝑥 = −4 into (2): Substituting 𝑥 = 3 into (2):
𝑦 = 1+𝑥 𝑦 =1+𝑥
= 1 + (−4) =1+3
= −3 =4
(−4, −3) (3, 4)

22
The Mathematics Digital Library (mathematics-dl.org)

Advanced (Question 1113)


Question 11(i)
𝑥 2 + 𝑥𝑦 + 𝑎𝑦 = 𝑏 … (1)
2𝑎𝑥 + 3𝑦 = 𝑏 … (2)
Substituting (2, 1) into (1):
(2)2 + 2(1) + 𝑎(1) = 𝑏
4+2+𝑎 =𝑏
6 + 𝑎 = 𝑏 … (3)
Substituting (2, 1) into (2):
2𝑎(2) + 3(1) = 𝑏
4𝑎 + 3 = 𝑏 … (4)
Equating (3) and (4):
6 + 𝑎 = 4𝑎 + 3
3𝑎 = 3
𝑎=1
Substituting 𝑎 = 1 into (3):
𝑏 =6+𝑎
=6+1
=7
CHECK: Substituting 𝑎 = 1 into (4):
𝑏 = 4(1) + 3
=7

Question 11(ii)
𝑥 2 + 𝑥𝑦 + 𝑦 = 7 … (1)
2𝑥 + 3𝑦 = 7 … (2)
From (2):
3𝑦 = 7 − 2𝑥
7 2
𝑦= − 𝑥 … (3)
3 3
Substituting (3) into (1):
7 2 7 2
𝑥 2 + 𝑥 ( − 𝑥) + ( − 𝑥) = 7
3 3 3 3

23
The Mathematics Digital Library (mathematics-dl.org)

7 2 7 2
𝑥2 + 𝑥 − 𝑥2 + − 𝑥 = 7
3 3 3 3
1 2 5 14
𝑥 + 𝑥− =0
3 3 3
Multiplying throughout by 3:
𝑥 2 + 5𝑥 − 14 = 0
Factorising:
(𝑥 + 7)(𝑥 − 2) = 0

𝑥+7=0 𝑥−2=0
𝑥 = −7 𝑥=2
Substituting 𝑥 = −7 into (3): Substituting 𝑥 = 2 into (3):
7 2 7 2
𝑦= − 𝑥 𝑦= − 𝑥
3 3 3 3
7 2 7 2
= − (−7) = − (2)
3 3 3 3
7 14 7 4
= + = −
3 3 3 3
21 3
= =
3 3
=7 =1
(−7, 7) – the “other” solution set (2, 1) – the solution set provided in the
question

24
The Mathematics Digital Library (mathematics-dl.org)

Question 12(i)
12𝑥 2 − 5𝑦 2 = 7 … (1)
Substituting (1, 𝑝) into (1):
12(1)2 − 5𝑝2 = 7
12 − 5𝑝2 = 7
Rearranging:
5𝑝2 = 12 − 7
=5
𝑝2 = 1
𝑝 = ±1

Question 12(ii)
12𝑥 2 − 5𝑦 2 = 7 … (2)
2𝑥 − 5𝑦 = 7 … (3)
From (3):
2𝑥 = 7 + 5𝑦 … (4)
Squaring (4):
4𝑥 2 = (7 + 5𝑦)2
= 49 + 25𝑦 2 + 70𝑦 … (5)
(5) × 3:
12𝑥 2 = 3(49 + 25𝑦 2 + 70𝑦)
= 147 + 75𝑦 2 + 210𝑦 … (6)
Substituting (6) into (2):
147 + 75𝑦 2 + 210𝑦 − 5𝑦 2 = 7
Rearranging:
70𝑦 2 + 210𝑦 + 140 = 0
Dividing throughout by 70:
𝑦 2 + 3𝑦 + 2 = 0
Factorising:
(𝑦 + 2)(𝑦 + 1) = 0

25
The Mathematics Digital Library (mathematics-dl.org)

𝑦 = −2 𝑦 = −1
2𝑥 = 7 + 5𝑦 2𝑥 = 7 + 5𝑦
= 7 + 5(−2) = 7 + 5(−1)
= 7 − 10 =7−5
= −3 =2
3 𝑥=1
𝑥=−
2
3 (1, −1)
(− , −2)
2

26
The Mathematics Digital Library (mathematics-dl.org)

Question 13(i)
𝐴 = 2(𝜋𝑟 2 ) + 2𝜋𝑟ℎ
32𝜋 = 2𝜋𝑟 2 + 2𝜋𝑟ℎ … (1)
Dividing (1) by 2𝜋:
32𝜋 2𝜋𝑟 2 + 2𝜋𝑟ℎ
=
2𝜋 2𝜋

16 = 𝑟 2 + 𝑟ℎ … (2) − 𝑠ℎ𝑜𝑤𝑛

Question 13(ii)
ℎ = 𝑟 + 4 … (3)
Substituting (3) into (2)
16 = 𝑟 2 + 𝑟(𝑟 + 4)
= 𝑟 2 + 𝑟 2 + 4𝑟
= 2𝑟 2 + 4𝑟 … (4)
Dividing (4) by 2:
8 = 𝑟 2 + 2𝑟
Rearranging:
0 = 𝑟 2 + 2𝑟 − 8
Factorising:
0 = (𝑟 + 4)(𝑟 − 2)
𝑟−2=0
𝑟=2
Substituting 𝑟 = 2 into (3):
ℎ =2+4
=6
Summary:
𝑟 = 2 𝑐𝑚
ℎ = 6 𝑐𝑚

27
The Mathematics Digital Library (mathematics-dl.org)

Dr. Lee is an experienced teacher who has taught at the


Singapore and Temasek Polytechnics. He currently teaches
at the Nanyang Technological University. A chemical
engineer by training, Dr. Lee feels that everyone benefits
from a solid grounding in mathematics, and that this
grounding can only be obtained through sufficient practice
on a variety of question types.
The solutions to each question are developed with care with
the idea of deepening the student’s number sense and
strengthening his basic technique of solving mathematical
problems. To this end, great attention has been paid to the
steps and explanations leading to the final answer.
Dr. Lee is the founder of several mathematics-related
initiatives, and can be contacted at ascklee@gmail.com.

28